Promoting adherence to cognitive-behavioral therapy for insomnia in the medically complex case - Lovell, Emily R., author; Eakman, Aaron, advisor; Weaver, Jennifer, committee member; Broussard, Josiane, committee member (Colorado State University. Libraries, 2023)
Objective. The purpose of this study is to explore how a medically complex case responded to cognitive-behavioral therapy for insomnia (CBT-I) in a community-based setting based on adherence to treatment recommendations. Method. A mixed-methods retrospective case study design was used to explore answers to two research questions: 1) How effective is CBT-I for an individual with insomnia comorbid with bipolar disorder? 2) How is CBT-I tailored for an individual with insomnia comorbid with bipolar disorder in a real-world setting? 3) How do we assess adherence to CBT-I delivered by an occupational therapist? Data sources included sleep diaries, service logs, pre-/post-treatment assessments, and interviews with the client and therapist. Results. Improvements in sleep latency, wake after sleep onset, early morning awakening, total sleep time, and sleep efficiency were observed. The most noteworthy improvements were a gain of almost two hours of total sleep time and a post-treatment SE of 95%. Likewise, scores on the Insomnia Severity Index, Epworth Sleepiness Scale, Sleep Disorders Symptoms Checklist-25, Dysfunctional Beliefs and Attitudes about Sleep scale, Sleep Hygiene Index, Quick Inventory of Depressive Symptomatology, and Patient Health Questionnaire-9 all improved to the extent that the client no longer met criteria for chronic insomnia. Overall adherence to the behavior components of CBT-I was very high. High motivation and scheduling and engaging in activities emerged as factors that promote adherence from the interview conducted with the client. A therapeutic relationship emerged as a factor that promotes adherence from the interview conducted with the therapist. Conclusion. CBT-I can be safely delivered by occupational therapists to individuals with bipolar disorder. Large improvements in sleep were observed and the client had high adherence to treatment protocols.
Keywords: bipolar disorder; insomnia; adherence; occupational therapy; cognitive-behavioral therapy for insomnia